An Analysis of POAC Management Functions in Local Agro-Industry in Mandailing Natal: An Islamic Managerial Ethics Perspective - Muhammad Ardiansyah; Rizka Ar Rahmah (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study examines the implementation of the POAC (Planning, Organizing, Actuating, and Controlling) management framework within a rural rice milling enterprise in Mandailing Natal, a predominantly Muslim regency, and interprets the findings through the lens of Islamic managerial ethics. Method: Using a single-case qualitative design, data were collected through in-depth interviews with the owner-manager and workers, direct observation, and document review. Analysis proceeded in two coding cycles: thematic coding aligned with the four POAC functions, followed by interpretive coding against Islamic ethical constructs derived from maqashid al-shariah. Results: All POAC components are present but operate in an informal, experience-based, and highly centralized manner. Planning is seasonal and intuitive, organizing relies on relational coordination without formal structure, actuating is conducted through participatory supervision, and controlling remains reactive and observational rather than system-driven. Islamic values are enacted personally rather than institutionally: amanah legitimises authority exercised without contract, adl secures fairness without written entitlement, tawazun and ihsan sustain the balance between commercial and communal obligation, while hisbah operates only as the owner's self-accounting and the prohibition of israf remains a moral disposition unsupported by loss measurement. Conclusion: Managerial integration is embedded in the owner's tacit knowledge and direct authority rather than in institutionalized procedures or performance metrics. The study advances the concept of ethically embedded POAC: Islamic values substitute for formal systems at micro scale, enabling operational flexibility and short-term stability while simultaneously constraining delegation, organizational learning, and scalability. Because ethics residing in a person can be neither audited, claimed, nor inherited, formalization is reframed not as an external imposition upon Islamic values but as the condition of their organizational durability. The study proposes a graduated, shariah-consistent institutionalization pathway beginning with the measurement of milling loss, thereby linking micro-level managerial dynamics with broader agro-industrial development discourse.